A multigene phylogeny of the eristaline flower flies (Diptera: Syrphidae), with emphasis on the subtribe Criorhinina. Issue 1 (6th April 2021) - Moran, Kevin M; Skevington, Jeffrey H; Kelso, Scott; Mengual, Ximo; Jordaens, Kurt; Young, Andrew D; Ståhls, Gunilla; Mutin, Valerii; Bot, Sander; van Zuijen, Menno; Ichige, Katsuyoshi; van Steenis, Jeroen; et al.
Abstract: We present the first multigene phylogeny focused on Eristalinae (Diptera: Syrphidae) utilizing a dataset containing 120 flower fly species from across all four subfamilies and representing 13 out of 16 tribes. Eight genes were used in the construction of the phylogeny: mitochondrial cytochrome c oxidase subunit I and the nuclear genes 28S ribosomal DNA, Alanylt RNA Synthetase, the carbamoyl phosphate synthase domain of CAD, Period, RNA-binding Protein 15 ( RBP –15, 5'), Casein Kinase 1 and TULP for a total of 6.7 kB of data. Eristalinae is recovered as paraphyletic with strong support for the elevation of Cerioidini, Merodontini and Volucellini to subfamilial status. Deineches, Flukea and Malometasternum render Criorhinina paraphyletic with respect to the type genus Criorhina . A clade with Criorhina, Matsumyia and Sphecomyia is strongly supported. The generic concept of Criorhina is paraphyletic, while Sphecomyia is monophyletic and Matsumyia is monophyletic but requires expansion. Evidence supports the resurrection of Romaleosyrphus and the creation of new genera. Criorhinina (stat. rev. ) is restricted to contain Criorhina, Matsumyia, Romaleosyrphus and Sphecomyia . Thirteen changes to the higher classification of Syrphidae are proposed.